Fifteen Minutes of Left Prefrontal Repetitive Transcranial Magnetic Stimulation Acutely Increases Thermal Pain Thresholds in Healthy Adults. (2007) - Borckardt, Jeffrey J; Smith, Arthur R; Reeves, Scott T; Weinstein, Mitchell; Kozel, F Andrew; Nahas, Ziad; Shelley, Neal; Branham, R Kyle; Thomas, K Jackson; George, Mark S
Abstract : BACKGROUND: Transcranial magnetic stimulation (TMS) of the motor cortex appears to alter pain perception in healthy adults and in patients with chronic neuropathic pain. There is, however, emerging brain imaging evidence that the left prefrontal cortex is involved in pain inhibition in humans. OBJECTIVE: Because the prefrontal cortex may be involved in descending pain inhibitory systems, the present pilot study was conducted to investigate whether stimulation of the left prefrontal cortex via TMS might affect pain perception in healthy adults. METHODS: Twenty healthy adults with no history of depression or chronic pain conditions volunteered to participate in a pilot laboratory study in which thermal pain thresholds were assessed before and after 15 min of repetitive TMS (rTMS) over the left prefrontal cortex (10 Hz, 100% resting motor threshold, 2 s on, 60 s off, 300 pulses total). Subjects were randomly assigned to receive either real or sham rTMS and were blind to condition. RESULTS: Subjects who received real rTMS demonstrated a significant increase in thermal pain thresholds following TMS. Subjects receiving sham TMS experienced no change in pain threshold. CONCLUSIONS: rTMS over the left prefrontal cortex increases thermal pain thresholds in healthy adults. Results from the present study support the idea that the left prefrontal cortex may be a promising TMS cortical target for the management of pain. More research is needed to establish the reliability of these findings, maximize the effect, determine the length of effect and elucidate possible mechanisms of action.